2021
DOI: 10.47941/jbsm.714
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organization Restructuring on Performance of Selected Media Firms in Kenya

Abstract: Purpose: The current study sought to establish the influence of organization restructuring on performance of selected media firms in Kenya. The study specifically sought to establish the influence of cost restructuring, governance reformation, downsizing and processes centralization on performance of selected media firms in Kenya. Methodology: The theories that guided the study includes Transaction Cost Theory, Agency Theory, Social Exchange Theory and Planned Change Theory. The study adopted a descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The study revealed that nature of formalization and layers in the organizational hierarchy has significant effects on the employee's performance of commercial banks in Anambra state. Other studies establishing the prominence of organizational structure on performance included Kinyua & Kihara (2021) in selected media firms in Kenya, Vithanage & Shyaman (2020) among Small and Medium Enterprises in Sri Lanka, and Funminiyi (2018) in North Central Nigeria among others.…”
Section: Regression Resultsmentioning
confidence: 99%
“…The study revealed that nature of formalization and layers in the organizational hierarchy has significant effects on the employee's performance of commercial banks in Anambra state. Other studies establishing the prominence of organizational structure on performance included Kinyua & Kihara (2021) in selected media firms in Kenya, Vithanage & Shyaman (2020) among Small and Medium Enterprises in Sri Lanka, and Funminiyi (2018) in North Central Nigeria among others.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Organizational restructuring occurred in the private sector and public sector. Research conducted by (Kinyua & Kihara, 2021) examines the effect of organizational restructuring on the private sector, while (Janet & Deya, 2018), (Kadir et al, 2021), (Mithe et al, 2019), and(Notanubun et al, 2019) examine the effect of restructuring on the public sector. This research was conducted in the public sector.…”
Section: Organization Restructuringmentioning
confidence: 99%
“…The dimensions of corporate restructuring are numerous. Prominent ones are strategy restructuring, process restructuring, organizational restructuring, manpower restructuring, market restructuring, financial restructuring, assets (business portfolio), capital structure, management/organizational, product restructuring, organizational restructuring, external restructuring, internal restructuring, downsizing, down scoping, business process reengineering, cost restructuring, governance reformation, departmentalization, decentralization, mergers, and acquisition ( Kinyua & Kihara, 2021).…”
Section: Dimensions Of Corporate Restructuringmentioning
confidence: 99%
“…The data were subjected to both descriptive and inferential statistical analysis and it was discovered that the bank's adoption of various restructuring strategies and specifically, the adoption of departmentalization, human resources restructuring, decentralization of processes, mergers, and acquisition had resulted in improved performance. Kinyua and Kihara (2021) examined the influence of organization restructuring on the performance of selected media firms in Kenya in a study designed to establish the influence of cost restructuring, governance reformation, downsizing, and processes centralization on the performance of three media firms (Nation Media Group, Royal Media Services, and Standard Group Limited). Using a total of 131 employees in the managerial positions of the selected media firms, data were analyzed using Pearson's correlation analysis and multiple regression analysis, the results show that cost restructuring, governance reformation, process centralization, and downsizing positively and significantly influence the performances of media firms and that an increase in one indicator increases the levels of performance.…”
Section: Corporate Restructuring and Organizational Performancementioning
confidence: 99%